Analysis of transmembrane domains and lipid modified peptides with matrix-assisted laser desorption ionization-time-of-flight mass spectrometry - Gerl, Mathias; Sachsenheimer, Timo; Grzybek, Michał; Coskun, Ünal; Wieland, Felix T.; Brügger, Britta (Analytical chemistry, 2014)
Protein-lipid interactions within the membrane are difficult to detect with mass spectrometry because of the hydrophobicity of tryptic cleavage peptides on the one hand and the noncovalent nature of the protein-lipid interaction on the other hand. Here we describe a proof-of-principle method capable of resolving hydrophobic and acylated (e.g., myristoylated) peptides by optimizing the steps in a mass spectrometric workflow. We then use this optimized workflow to detect a protein-lipid interaction in vitro within the hydrophobic phase of the membrane that is preserved via a covalent cross-link using a photoactivatable lipid. This approach can also be used to map the site of a protein-lipid interaction as we identify the peptide in contact with the fatty acid part of ceramide in the START domain of the CERT protein.
Gesehen am 01.09.2020